2013
DOI: 10.1007/978-3-642-38919-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Respiratory Syncytial Virus Vaccines

Abstract: Reactive airway disease (RAD) is a general term for respiratory illnesses manifested by wheezing. Respiratory syncytial virus (RSV) results in wheezing, either by causing bronchiolitis or by inducing acute exacerbations of asthma. There has been a long standing interest in whether severe RSV bronchiolitis in infancy is a risk factor for the development of asthma later in childhood. While epidemiologic studies have suggested that such a link exists, a very recent study suggests that infants with greater airways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A study in Cameroon showed that RSV circulated in the beginning of the dry season from October to December at 5.7% in outpatients with influenza-like illness visiting influenza surveillance centers in 2009. Another study recently showed that RSV was the second most common respiratory virus (13.3%) after human adenovirus in children hospitalized in Yaoundé, Cameroon [14,15]. The unicentric study did not find a significant age-specific RSV prevalence, which might have underestimated the overall detection rate for selected viruses.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Cameroon showed that RSV circulated in the beginning of the dry season from October to December at 5.7% in outpatients with influenza-like illness visiting influenza surveillance centers in 2009. Another study recently showed that RSV was the second most common respiratory virus (13.3%) after human adenovirus in children hospitalized in Yaoundé, Cameroon [14,15]. The unicentric study did not find a significant age-specific RSV prevalence, which might have underestimated the overall detection rate for selected viruses.…”
Section: Introductionmentioning
confidence: 99%